FIGURE 19 in Morphological features of larvae of Pandalus eous, P. goniurus, and P. tridents (Decapoda, Pandalidae) from planktonic samples taken in marine waters near Kamchatka Peninsula - Sedova, Nina; Grigoriev, Sergey (Zenodo, 2017)
FIGURE 19. Morphology features of Pandalus tridens. Third zoeal stage. Abbreviations above in Materials and methods. Scale: 1 mm.